The Effect of Cognitive Therapy on Medication Adherence in Mental Patients with Schizophrenia - Masithoh, Anny Rosiana; Faridah, Umi; Rahmawati, Amalia (GLOBAL HEALTH SCIENCE GROUP, 2024)
Schizophrenia is a severe mental disorder that is unable to recognize realistically and loses self-view or is unable to assess oneself or measure one's own strengths and weaknesses. One of the causes of schizophrenia is psychological factors, namely the inability to overcome existing problems. Objective : to determine the effect of cognitif therapy on adherence to taking medication in patients with mental disorders with schizophrenia at the Jekulo Kudus Jalma Sehat Foundation. Method: The type of this research is a quasi-experimental with a cross-sectional approach, the population of this study is 63 respondents. Results: The results of the statistical analysis of the Willcoxon test obtained p value = 0.001 which is less than the significance level ɑ <0.05. then Ho is rejected and Ha is accepted. there is